Child Abuse and Neglect; Recognize, Respond and Report: A Cross-Sectional Study - Trupti Jain; Jaya Singh; Dinesh Raja; Akhilesh Chandra; Mahesh Khairnar; Rahul Agrawal (RUHS Journal of Health Sciences, 2023)
Child abuse and neglect (CAN) is a significant global problem with a serious impact on the victims throughout their lives. Dentists have a unique opportunity to address this problem. The aim of this study was to assess the knowledge and prevalence of child abuse and neglect amongst undergraduate students of the faculty of Dental Sciences, Banaras Hindu University (BHU), Varanasi, and to create awareness about child abuse and behavioural patterns.